Live cell micropatterning reveals the dynamics of signaling complexes at the plasma membrane - Löchte, Sara (J Cell Biol, 2014)
Interactions of proteins in the plasma membrane are notoriously challenging to study under physiological conditions. We report in this paper a generic approach for spatial organization of plasma membrane proteins into micropatterns as a tool for visualizing and quantifying interactions with extracellular, intracellular, and transmembrane proteins in live cells. Based on a protein-repellent poly(ethylene glycol) polymer brush, micropatterned surface functionalization with the HaloTag ligand for capturing HaloTag fusion proteins and RGD peptides promoting cell adhesion was devised. Efficient micropatterning of the type I interferon (IFN) receptor subunit IFNAR2 fused to the HaloTag was achieved, and highly specific IFN binding to the receptor was detected. The dynamics of this interaction could be quantified on the single molecule level, and IFN-induced receptor dimerization in micropatterns could be monitored. Assembly of active signaling complexes was confirmed by immunostaining of phosphorylated Janus family kinases, and the interaction dynamics of cytosolic effector proteins recruited to the receptor complex were unambiguously quantified by fluorescence recovery after photobleaching.